Measuring co-movements of CDS premia during the Greek debt crisis - Sergio Andenmatten; Felix Brill (University of Bern, Department of Economics, 2011)
In this paper we test whether the co-movement of sovereign CDS premia increased significantly after the Greek debt crisis started in October 2009. We perform a bivariate test for contagion that is based on an approach proposed by Forbes and Rigobon (2002). Our sample consists of daily data between October 2008 and July 2010 for 39 countries including both emerging and industrialized countries. Our results indicate that there were periods of contagion for CDS markets during the Greek debt crisis, which is in contrast to the results from Forbes and Rigobon (2002) for equity markets after the Hong Kong crash and their conclusion of no contagion, only interdependence. Especially for European countries we would instead conclude both contagion and interdependence.
Keywords: C58; G01; G12; G15; 330; CDS market; Contagion; Greek debt crisis; Sovereign credit; Kreditderivat; Ansteckungseffekt; Öffentliche Schulden; Staatsbankrott; Griechenland; Länderrisiko; Risikoprämie; Welt